Ethic and humanities themes insertion in medical integrate curriculum at public school of medicine in Federal District Of Brazil - Carvalho Garbi Novaes, Maria Rita; Garcez Novaes, Luiz Carlos; Guilhem, Dirce; Lolas, Fernando (Acta Bioethica, 2009)
Objective: To establish a diagnosis of the insertion of bioethics, ethics and humanistic values and attitudes to the program of the Medical School of ESCS - Escola Superior em Ciências da Saúde, public school of medicine, Distrito Federal, Brazil, in order to contribute to the process of curricular management. Methodology: The study is cohorte and documental. Thirty-two indicators to the thematic on ethics and twenty-four related to humanization were utilized. The educational purpose and contents of activities in modules such as thematic, abilities, interaction and attitude towards the community for teaching and services, from first to senior years as well as in boarding schools programs were all analyzed in the Medical School curriculum of ESCS (2006) and about the pedagogic project of the Course (2001). Results: It was observed a greater insertion of thematic related to ethics and bioethics in the initial levels of the course, Freshman and Sophomore including boarded students, when compared to the insertion in Junior and Senior clerkship years (IC95%-a=0,034, pvalue=0,007). The unit on abilities and attitudes was the axle which presented greater recurrence of the thematic on humanization in programs of 1ª and 4ª years (IC95%-a=0,026, pvalue=0,013). It was observed an increase in the recurrence of the thematic on humanization developed in thematic modules and interaction community-teaching/service in the 2ª year and decline in the subsequent ones. The results were very low in the 3ª and 4ª years. When compared with the clerkship it was observed that the first four series had greater insertion of such thematic (IC95%-a=0,042, pvalue=0,029). Conclusion: The academic program developed in the year of 2006 at ESCS presented improvements when compared to the pedagogical project of the course.